Low‐Temperature Methanol‐Water Reforming Over Alcohol Dehydrogenase and Immobilized Ruthenium Complex. Issue 18 (10th August 2021) - Shen, Yangbin; Wang, Luqi; Xu, Ziwen; Ning, Fandi; Zhan, Yulu; Bai, Chuang; Zhou, Xiaochun
Abstract: Hydrogen is one of the most promising sustainable energy carriers for its high gravimetric energy density and abundance. Nowadays, hydrogen production and storage are the main constraints for its commercialization. As a current research focus, hydrogen production from methanol‐water reforming, especially at low temperature, is particularly important. In this study, a novel reaction path for low‐temperature methanol reforming through synergistic catalysis was developed. Alcohol dehydrogenase (ADH) and coenzyme I (nicotinamide adenine dinucleotide, NAD + ) were employed for methanol catalytic dehydrogenation at low temperature, which could generate formaldehyde and reductive coenzyme I (NADH). Covalent triazine framework‐immobilized ruthenium complex (Ru‐CTF) was prepared afterwards. On one hand, the catalyst exhibited high activity for the formaldehyde–water shift reaction to generate hydrogen and carbon dioxide. On the other hand, the NADH dehydrogenation was also catalyzed by the Ru‐CTF, producing NAD + and hydrogen. Additionally, the catalyst also showed high biocompatibility with ADH. Through the synergistic effect of the above two main processes, methanol could be converted into hydrogen and carbon dioxide stably at low temperature for more than 96 h. The hydrogen production rate was dependent on the pH of the reaction solution as well as the ADH dosage. A hydrogen production rate of 157 mmol h −1 mol −1 Ru was achieved at the optimum pH (8.1). Additionally, the hydrogen production rate increased linearly with the ADH dosage, reaching 578 mmol h −1 mol −1 Ru when the ADH dosage was 180 U at 35 °C. This research could not only help overcome the difficulties for methanol reforming near room temperature but also give new inspiration for designing new reaction pathways for methanol reforming. Abstract : Synergistic when wet : Methanol is fully converted to hydrogen and carbon dioxide near room temperature. Methanol‐water reforming is catalyzed by alcohol dehydrogenase (ADH) and immobilized ruthenium complex. respectively. Through the synergistic effect of the main processes, CH3 OH→HCHO→H2 and CH3 OH→NADH→H2, methanol is stably converted into hydrogen and carbon dioxide at low temperature for more than 96 h.